116. Antiviral Activity and Safety of Long-acting Cabotegravir (CAB LA) Plus Long-acting Rilpivirine (RPV LA), Administered Every 2 Months (Q2M), in Hiv-positive Subjects: Results from the POLAR Study. (31st December 2020) - Mills, Anthony; Richmond, Gary J; Newman, Cheryl; Osiyemi, Olayemi; Cade, Jerry; Brinson, Cynthia; De Vente, Jerome; Andany, Nisha; Margolis, David; Sutton, Kenneth; Wilches, Viviana; Roberts, Jeremy; et al.
Abstract: Background: Long-acting (LA) cabotegravir (CAB) and rilpivirine (RPV) injectable suspensions have demonstrated efficacy in phase III studies. POLAR assessed antiviral activity and safety of CAB LA+RPV LA, administered every 2 mos (Q2M), in HIV-1 infected, antiretroviral therapy–experienced adults who completed LATTE and received once-daily oral CAB30mg+RPV25mg treatment. Methods: POLAR is a phase IIb, multicenter, open-label, rollover study in 97 virologically suppressed, HIV-infected adults. LATTE participants who completed ≥312 weeks on study, with plasma HIV-1RNA< 50c/mL at screening, were eligible for POLAR and offered the option to switch to CAB LA+RPV LA Q2M or to the oral fixed dose combination of dolutegravir (DTG)/rilpivirine (RPV) once daily, for continued maintenance of HIV-1RNA suppression. 90 participants chose CAB LA+RPV LA and 7 participants chose oral DTG/RPV. The primary outcome measure was proportion of participants with plasma HIV-1RNA≥50c/mL after 12 mos (M12) of therapy. Safety and laboratory measures were assessed throughout the study. Participants selecting LA treatment completed satisfaction and quality-of-life questionnaires at Day 1, M6, and M12. Results: At M12, no participant had HIV-1RNA≥50c/mL or protocol defined virologic failure (confirmed plasma HIV-1RNA > 200c/mL). Excluding injection-site reactions (ISRs), nasopharyngitis (11%), upper respiratory tract infection (11%), diarrhea (10%), and pyrexia (10%) were the most commonly reported adverse events (AEs) in the Q2M arm. 10% (9/90) of Q2M participants reported AEs ≥grade 3; 0 were drug related. 2% (2/90) of Q2M participants had AEs leading to withdrawal. 6% (5/90) of participants reported serious AEs (1 considered drug-related). Over 12 mo, 1534 injections were administered; 463 ISRs were reported (30%; all grade 1/2 [84%/16%]); resolution of ISRs occurred after a median of 3 days. Minimal changes in lab parameters were observed in participants across 12 mo. 88% of participants who received LA therapy preferred CAB LA+RPV LA vs oral therapy. Table 1 Table 2 Conclusion: CAB LA+RPV LA, administered Q2M, resulted in durable virologic suppression, an acceptable tolerability profile, and high levels of participant satisfaction over the first 12 mo of treatment in POLAR. Disclosures: Anthony Mills, MD, Gilead (Grant/Research Support, Advisor or Review Panel member)Janssen Pharmaceutica (Grant/Research Support, Advisor or Review Panel member)Merck (Grant/Research Support, Advisor or Review Panel member)Shionogi (Grant/Research Support)ViiV Healthcare (Grant/Research Support, Advisor or Review Panel member) Gary J. Richmond, MD, FACP, FCCP, Gilead (Scientific Research Study Investigator)TaiMed (Scientific Research Study Investigator)Viv (Scientific Research Study Investigator) Cheryl Newman, MD, Gilead (Grant/Research Support)GlaxoSmithKline (Grant/Research Support, Speaker's Bureau)ViiV Healthcare (Research Grant or Support, Speaker's Bureau) Olayemi Osiyemi, M.D, GlaxoSmithKline (Advisor or Review Panel member, Speaker's Bureau)ViiV Healthcare (Advisor or Review Panel member, Speaker's Bureau) Jerry Cade, MD, Gilead (Consultant, Research Grant or Support, Speaker's Bureau)Janssen Pharmaceutica (Consultant)Merck (Consultant, Research Grant or Support, Speaker's Bureau)ViiV Healthcare (Consultant, Research Grant or Support) Cynthia Brinson, MD, Gilead (Advisor or Review Panel member, Speaker's Bureau)ViiV Healthcare (Advisor or Review Panel member, Speaker's Bureau) Nisha Andany, MD, MPH, FRCPC, Gilead Sciences (Scientific Research Study Investigator)GlaxoSmithKline (Scientific Research Study Investigator)Janssen (Scientific Research Study Investigator) David Margolis, MD, MPH, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee) Kenneth Sutton, MA, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee) Viviana Wilches, HBSc, MBiotech, GlaxoSmithKline (Employee, Shareholder) Jeremy Roberts, MSc, GSK (Employee) Cynthia C. McCoig, MD, ViiV Healthcare (Employee) Kati Vandermeulen, MSC, Janssen Pharmaceutica (Employee, Shareholder) William Spreen, PharmD, ViiV Healthcare (Employee, Shareholder)